2000
DOI: 10.1247/csf.25.171
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Recombinant Human Cytokeratin 19 to Laminin. A Possible Role in Interaction between Intermediate Filament Derived from Epithelial Cells and Extracellular Matrixes.

Abstract: ABSTRACT. Cytokeratin 8 (CK8) and cytokeratin 19 (CK19) is a specific cytoskeletal component of simple epithelia, including bronchial epithelial cells. We hypothesized that CK8 or CK19 released from epithelial cells may bind to and cause damage to extracellular matrixes through binding of anti-CK8 or anti-CK19 autoantibodies. In the present study, bindings of recombinant human CK8 and CK19 to laminin (both derived from mouse sarcoma cells and human), collagen, gelatin, and fibronectin were evaluated by a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
1
8
0
1
Order By: Relevance
“…Induction of keratin expression by laminin through its receptors on cell surface also was observed in HCC cells (24). Together with the finding that released keratin may cause basement membrane damage through binding to laminin (25), we hypothesize that the mAb T2-2 functions as an inhibitor of tumor cell migration and expansion through a laminin-mediated pathway that prevents matrix degradation and controls cell survival. Importantly, more details in cell signaling will need to be elucidatd.…”
Section: Discussionsupporting
confidence: 58%
“…Induction of keratin expression by laminin through its receptors on cell surface also was observed in HCC cells (24). Together with the finding that released keratin may cause basement membrane damage through binding to laminin (25), we hypothesize that the mAb T2-2 functions as an inhibitor of tumor cell migration and expansion through a laminin-mediated pathway that prevents matrix degradation and controls cell survival. Importantly, more details in cell signaling will need to be elucidatd.…”
Section: Discussionsupporting
confidence: 58%
“…7 Another study found that CK19 was correlated with vascular invasion in HCC. 24 We think this may be because of the differences in patient backgrounds; furthermore, those with CK19 may have had a low incidence of vascular invasion as its ICC-like presentation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al proposed that HCC could be classified by the presence or absence of CK19 expression, based on the evidence that HCC could originate from hepatic progenitor cells, 3,4,6 which could retain its biliary marker (cytokeratin 19 [CK19]) and progenitor cell marker (OV-6) during its differentiation into HCC. 6 CK19 was an important structural component of the epithelial cytoskeleton, generally expressed on cholangiocytes and intrahepatic cholangiocarcinoma (ICC) cells, 7,8 and HCCs positive for CK19 were found to have ICC-like differentiation associated with poorer differentiation, higher level of cellular proliferation, and poorer survival. 3,4,6,9 Although the incidence of lymph node metastasis (LNM) in operable HCC is as low as 1.7% to 7.5%, 10,11 lymph node (LN) status is a definite prognostic factor in HCC and leads to generally dismal survival rates.…”
mentioning
confidence: 99%
“…Interestingly, some authors suggest K19 provides tumour cells with a higher metastatic potential by promoting extracellular matrix degradation and/or cell mobility [31,32]. In a murine tumour model Chu et al established that cells expressing intact keratins had higher in vitro mobility and invasiveness [33].…”
Section: Discussionmentioning
confidence: 99%